From Fitness Tracking to Augmented Shopping Experience: Perceptions and Use of Mobile Payment among Runners Using Wearable Devices - Özlem Özdinç (Türk Spor ve Egzersiz Dergisi)
Regularly exercising users of sports wearables (e.g., smartwatches) comprise an overlooked group in the literature on mobile payment despite their frequent use of such high-tech devices that allow making mobile payments. Payment-capable wearables could lead to a more health-conscious shopping experience through push notifications that make customised suggestions―say, for fluid/food intake based on dehydration/calories burnt, since they track exercise (e.g., steps), health (e.g., pulse), and well-being data (e.g., sleep cycles). Accordingly, this study aims to explore the perceptions and use of mobile payment technology among a sample of runners, who track their exercise metrics using sports wearables. A typical runner that we captured data from was an educated, employed, and adult female user of high-tech sports wearables, who makes nearly 9 kilometres on each of her four runs in a week, but taps her smartphone―not her wearable―to make payments for necessity goods (e.g., food, apparel) and services (e.g., bills, bookings) through either Alipay or Apple Pay. Mobile payment was among the top three preferred methods of payments; however, only 4% were using their wearable device for that purpose. Runners’ had a positive perception of the mobile payment technology, which was homogeneous across the categories of their socio-demographic characteristics and exercise metrics. These results indicate that mobile payment use on a smartphone is common among the physically active, but the convergence of that technology with high-tech wearable devices is yet to find acceptance.